Studi Kualitatif Perilaku Pekerja dalam Pengendalian Risiko Kebakaran di Area Filling Shed Fuel Terminal Meulaboh - M.Haris Safandi; Jun Musnadi Is; Wintah Wintah; Onetusfifsi Putra; Yarmaliza Yarmaliza (KOLONI, 2026)
The filling shed is a high-risk area for fire due to the presence of fuel vapors, static electricity, and operational activities that can serve as ignition sources. Although the company has implemented various control measures, worker behavior remains a critical factor in successful fire prevention. This study aims to analyze worker behavior regarding fire risk control in the filling shed area of ​​PT Pertamina Patra Niaga’s Meulaboh Fuel Terminal. A qualitative approach with a descriptive phenomenological design was employed. Data were gathered through in-depth interviews and participant observation involving seven informants selected via purposive sampling, and subsequently analyzed using the Miles and Huberman model. The results indicate that while workers possess good knowledge of safety procedures, their implementation is not yet fully consistent. Issues identified include the normalization of risk regarding fuel vapor exposure, suboptimal use of Personal Protective Equipment (PPE) due to comfort concerns, lower compliance among tanker truck crews compared to internal operators, and inconsistent reporting of near-miss incidents. The study concludes that fire risk control depends not only on the availability of facilities and procedures but also on the consistency of worker behavior. Therefore, strengthening the safety culture, raising worker awareness, and providing more ergonomic PPE are essential to support safe work practices.